Budgeting challenges on the path towards universal health coverage: The case of Benin - Elisabeth Paul; N'koué Emmanuel Sambiéni; Jean-Pierre Wangbe; Fabienne Fecher; Marc Bourgeois (Health Economics Review, 2020)
Background: In its pursuance of universal health coverage (UHC), the government of Benin is piloting a project of mandatory social insurance for health entitled "ARCH". Methods: We analysed budget data and ARCH documents, and conducted four observation missions in Benin between March 2018 and January 2020. Results are presented in terms of the three classical objectives of public expenditure management. Results: The government of Benin faces important budgeting challenges when it comes to implementing the ARCH social insurance project: (i) the fiscal space is quite limited, there is a limited potential for new taxes and these may not benefit the ARCH funding, hence the need to prioritise fiscal resources without jeopardising other areas; (ii) the purchasing of health services should be more strategic so as to increase allocative efficiency and equity; (iii) the efficiency of the expenditure process needs to be improved, and more autonomy needs to be devoted to the operational level, so as to ensure that health facilities are reimbursed in a timely fashion in order to meet insured people's health costs, in such a way as to avoid jeopardizing the financial equilibrium of these facilities. Conclusion: The important budgeting challenges faced by Benin when it comes to implementing its UHC policy are also faced by many other African countries. It is important to avoid a situation in which the resources dedicated by the government to the social health insurance system are at the expense of a reduction in the financing of preventive and promotional primary healthcare services.
Keywords: 330; Universal health coverage; Health financing; Budgeting; Public expenditure management; Strategic purchasing; Benin